On p→(x)-Anisotropic Problems with Neumann Boundary Conditions - Anass Ourraoui (International Journal of Differential Equations)
This work is devoted to the study of a general class of anisotropic problems involving p→(·)-Laplace operator. Based on the variational method, we establish the existence of a nontrivial solution without Ambrosetti-Rabinowitz type conditions.